Inkjet‐ and FlexTrail‐Printing with Low Silver Consumption for Silicon Heterojunction Solar Cells. Issue 9 (11th June 2019) - Schube, Jörg; Fellmeth, Tobias; Jahn, Mike; Keding, Roman; Glunz, Stefan W.
Abstract : Bifacial busbarless silicon heterojunction (SHJ) solar cells with an edge length of 156.8 mm are metalized using a commercially available Ag nanoparticle ink on the front side. By means of inkjet‐printing, a maximum conversion efficiency of 23.3% is achieved. The influence of the inkjet‐printed layer number per contact finger, which is varied from one to five, on cell performance is investigated in detail. Optima are found for one and two layers, which ensure both high efficiency and low silver consumption. Furthermore, a novel metallization technology, called FlexTrail‐printing, is introduced. Using the same ink as in the case of inkjet‐printing, the finger width is reduced from 75 ± 1 to 16 ± 1 μm. This results in an enhanced short‐circuit current density and, therefore, a maximum conversion efficiency of 23.7%. Only 0.3 ± 0.1 mg Ag nanoparticle ink (deposited at 25 °C substrate temperature) is consumed during FlexTrail‐printing on a large‐area wafer (area of 244.3 cm 2 ) with a front grid of 80 fingers. Abstract : Using inkjet‐printing, a conversion efficiency of heterojunction solar cells of 23.3% is achieved. Furthermore, a novel metallization technology, called FlexTrail‐printing, is introduced. Utilizing a commercially available silver nanoparticle ink, the finger width is reduced to 16 ± 1 μm. Thereby, a conversion efficiency of 23.7% is achieved. Simultaneously, only 0.3 ± 0.1 mg ink per grid is consumed.